ASHMI™ induced long-lasting tolerance to allergen exposure in an asthma model is interferon - γ, but not TGF-β dependent - Srivastava, Kamal (2010)
Chronic allergic asthma is the result of a Th2- biased immune status. Current asthma therapies control symptoms in some patients, but a long lasting therapy has not been established. ASHMI™, a Chinese herbal formula improved symptoms and lung function, and reduced Th2 responses in a controlled trial of patients with persistent moderate to severe asthma. We evaluated the persistence of ASHMI™ beneficial effects following therapy in a murine model of persistent asthma and the immunological mechanisms underlying such effects. BALB/c mice sensitized intraperitoneally with ovalbumin (OVA) received 3 weekly intratracheal OVA challenges to induce airway hyperreactivity (AHR) and inflammation (OVA mice). Additional OVA mice were treated with ASHMI™ (OVA/ASHMI™) or water (OVA/Sham) for 4 weeks, and then challenged immediately and eight weeks post-therapy. In other experiments OVA mice received ASHMI™ treatment with concomitant neutralization of IFN-γ or TGF-β. Effects on airway responses, cytokine and OVA-specific IgE levels were determined 8 weeks post-therapy. Prior to treatment, OVA mice exhibited AHR and pulmonary eosinophilic inflammation following OVA challenge, which was almost completely resolved immediately after completing treatment with ASHMI™ and did not re-occur following OVA re-challenge up to 8 wks post-therapy. Reduced allergen-specific IgE and Th2 cytokine levels, and increased IFN-γ levels also persisted at least 8 wks post-therapy. ASHMI™ effects were eliminated by neutralization of IFN-γ, but not TGF-β, during therapy. CONCLUSION: ASHMI™ induced long-lasting post-therapy tolerance to antigen-induced inflammation and AHR. IFN-γ is a critical factor in ASHMI™ effects.